‘If You Don't Speak Up, It Will Eat You Up’: A Critical Discourse Analysis of Voice and Silence in a Multicultural Clinical Healthcare System - Shaista Salman Guraya; Farah Ennab; Hafidh Mohammad Khamis AlRajaby; Ibrahim Inuwa; Entesar Al Hammadi; Manal Al Halabi; Nabil Zary (Nursing Inquiry, 2026)
ABSTRACT Despite sustained efforts to promote speaking up in healthcare, improvements remain ephemeral. In diverse clinical learning and practice environments shaped by generational, cultural, professional and pedagogical plurality, speaking up operates as a situated social practice. Adopting an interpretive bricolage, we conducted a critical discourse analysis of interviews with 17 healthcare professionals within a multicultural academic health system. We identified four definitional discourses and eight interpretive repertoires through which participants legitimised voice using different moral and relational logics, including loyalty, conscience, professionalism, discernment, relational navigation, procedural alignment and emotional authenticity. Only one repertoire, most prominent among residents, constructed speaking up as self‐combustion, where voicing concerns threatened professional survival. These findings suggest that dominant solutions centred on communicative competence and psychological safety are incomplete. Stewardship‐based repertoires enabled voice without reliance on either construct, while ‘wasta’ functioned not as corruption but as relational social capital enabling culturally intelligible action. Speaking up, therefore, emerged as a chameleon concept whose meaning shifts across contexts. Attempting to capture speaking up through another abstract construct risks a shotgun approach. Rather than treating voice as a discrete behaviour to be taught, speaking up may be better understood as a situated judgement shaped by hierarchy, legitimacy and relational consequence.